The 80th Anniversary of the Warsaw Ghetto Uprising: An Attempt at a Summary - Taczyńska Katarzyna (Eastern European Holocaust Studies, 2023)
The review discusses the 80th anniversary of the Warsaw Ghetto Uprising’s celebrations in Poland.